O olhar da comissão assessora de avaliação sobre o enade da área de pedagogia - 2005 - Bordas, Merion Campos; Almeida, Ana Maria Freire Da Palma Marques De [UNESP]; Dalben, Ângela Imaculada Loureiro De Freitas; Ramalho, Betania Leite; Freitas, Helena Lopes De; Cavalcante, Lucíola Inês Pessoa; Bittar, Mariluce (Publicação da Rede de Avaliação Institucional da Educação Superior (RAIES), da Universidade Estadual de Campinas (UNICAMP) e da Universidade de Sorocaba (UNISO)., 2008)
This paper presents the work conducted between May and November of 2005 by the Evaluation Assistance Committee of the National Student Performance Exam (ENADE) in the field of Pedagogy. The purpose of the Committee is to present guidelines, objectives and other specifications that contribute to the construction of evaluation tools to be provided to in-coming and graduating students who participate in the 2005 Exam. The text begins with a brief historic recapitulation of the trajectory of Pedagogy Programs in Brazil, in legal and situational terms. The analysis emphasizes the context of these Programs in 2005, one that is marked by the absence of properly approved National Curriculum Guidelines. Given this fact the Assistance Commission addressed the impact of the various elements in this situation and the discussions and tensions that still mark the daily life of the Pedagogy Programs, considering the propositions of the national movement in light of the determinations of SINAES. The guiding parameters of the matrixes for the construction of the instruments - the knowledge and abilities required - are based on the definitions of the profile of the pedagogue and of the fields of activity consecrated in the documents approved by the representative entities in the field, which have guided the curricular organization of most of the operating programs. Respecting the principles defined by SINAES and ENADE for the establishment of a national evaluation policy for Higher Education, the Commission guided all of the phases of its work by the concept of evaluation as an instrument of articulation of knowledge, to encourage mutual cooperation and solidary educational practices. Considered as a public and not only technical issue, which is supported by an ethical and political commitment in defense of the public and social character of the university, the evaluation has consequences that go beyond this institution and has important repercussions for society.

Este artigo apresenta o trabalho realizado entre maio e novembro de 2005, pela Comissão Assessora de Avaliação do Exame Nacional de Desempenho dos Estudantes (ENADE) da área da Pedagogia, incumbida de propor diretrizes, objetivos e outras especificações para a construção dos instrumentos de avaliação a serem aplicados aos estudantes ingressantes e concluintes participantes do Exame de 2005. Após uma breve recapitulação histórica da trajetória dos Cursos de Pedagogia no país, em termos legais e situacionais, é destacado o contexto, marcado pela ausência de Diretrizes Curriculares Nacionais devidamente aprovadas, no qual ainda se situavam esses Cursos em 2005. Nesse sentido, a Comissão Assessora trabalhou sob o impacto da conjugação dos fatores da realidade e das discussões e tensões que ainda marcavam o cotidiano dos Cursos de Pedagogia, procurando contemplar as proposições do movimento nacional à luz das determinações do SINAES. Os parâmetros orientadores das matrizes para a construção dos instrumentos - conhecimentos e habilidades demandados - partiram das definições do perfil do Pedagogo e das áreas de atuação consagradas nos documentos aprovados por entidades representativas da área, os quais têm orientado a organização curricular da maioria dos cursos ora em desenvolvimento. Respeitados os princípios estabelecidos pelo SINAES e pelo ENADE na definição de uma política nacional de avaliação do Ensino Superior, a Comissão orientou todas as etapas de seu trabalho pela concepção de avaliação como instrumento de articulação de saberes, num estímulo à mútua cooperação e às práticas formativas solidárias. Tomada como uma questão pública e não só técnica, tendo como suporte o compromisso ético-político com a defesa do caráter público e social da instituição universitária, a avaliação tem, pois, conseqüências não apenas restritas ao seu âmbito, mas com repercussões importantes para a sociedade.
The perspective of the evaluation assistance committee concerning enade in the field of pedagogy 2005
Keywords: Higher education evaluation; ENADE; Pedagogy; Avaliação da educação superior; ENADE; Pedagogia